2020
DOI: 10.5144/0256-4947.2020.482
|View full text |Cite
|
Sign up to set email alerts
|

Survival after therapy for pediatric ependymoma in a tertiary care center in Saudi Arabia

Abstract: BACKGROUND: There is limited data from Saudi Arabia on the demographic characteristics, outcomes and effectiveness of different treatment modalities in children with intracranial ependymoma. OBJECTIVE: Study the characteristics of pediatric ependymoma and outcomes of treatment modalities in Saudi Arabia. DESIGN: Retrospective. SETTING: Tertiary care center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The management of children with ependymoma is still a controversial topic in paediatric neuro-oncology and may vary among institutions, from only-surgery to a combination of surgery, RTH, CTH or even autologous hematopoietic stem cell transplant (autoHSCT, Table A1 ) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of children with ependymoma is still a controversial topic in paediatric neuro-oncology and may vary among institutions, from only-surgery to a combination of surgery, RTH, CTH or even autologous hematopoietic stem cell transplant (autoHSCT, Table A1 ) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Discussionmentioning
confidence: 99%
“…et al (2021) [ 54 ]/R 386 Cranial S + pRTH + CTH (30%) 7 y PFS, OS: 64%, 82% R0, female sex, infratentorial site Lundar T. et al (2021) [ 55 ]/R 26 Cranial S + RTH (69%) + CTH (11%) 5 y OS: 26% (early period of the study), 73% (late period) Later time of the treatment, MRI-era Lundar T. et al (2021) [ 56 ]/R 33 Spinal S + RTH (27%) 10 y OS: 67% Not found Shah S.N. et al (2020) [ 57 ]/R 22 Cranial S + RTH (77%) + CTH (23%) 5 y OS: 55% Not found Massimino M. et al (2021) [ 58 ]/P * 160 Cranial S + RTH + CTH 5, 10 y PFS & OS: 66%, 58% & 80%, 73% R0, lower histologic G, molecular features Abbreviations: &—and; AHSCT—autologous hematopoietic cell transplant; CSS—cancer specific survival; CTH—chemotherapy; FFS—failure-free survival; G—grade; hRTH—hypofractionated radiotherapy; IMRT—intensity modulated radiotherapy; mets—metastases; MRI—magnetic resonance imaging; N—number of patients; OS—overall survival; P—prospective; PFS—progression-free survival; pRTH—proton radiotherapy; R—retrospective; RTH—radiotherapy; R0—radical resection (macro- and microscopically); R1—macroscopically radical resection (but not microscopically); R2—macroscopically not-radical resection; S—surgery; SRS—stereotactic radiosurgery; y—year; y/o—year old; vs.—versus; * update of the study from 2016, reference number 10.
Figure A1 The schema of the study—treatment applied and outcome of th...
…”
Section: Table A1mentioning
confidence: 99%